Introduksi Bahan Bakar Wood Pellet pada IKM Makanan - Syamsudin Syamsudin; Aflit Nuryulia Praswati; Siti Fatimah Nurhayati; Siti Zulaekah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Small and Medium Enterprises (IKM) play an important role in the economic growth of Sragen Regency. Efforts to empower SMEs to need to be continued, one of which is by maintaining the availability of fuel. The IKM of Kedawung District currently uses wood fuel but is hampered by the quality of firewood that is less dry. Nata de coco IKM had switched to using LPG, but it was often difficult to get it if they found it at a high price. Wood pellets are an alternative fuel source that can be used by SMIs in Sragen Regency. Sragen Regency already has wood pellet producers located in Kalijambe District. The solution offered at IKM is alternative energy biomass wood pellets. The Community Partnership Program (PKM) to be carried out is in the form of production in the form of introduction of wood pellet biomass energy and management in the form of calculating the feasibility of using wood pellets for business development. The PKM activity plan includes training and socialization of wood pellet biomass energy, the introduction of wood pellet stoves, training on the use of wood pellet stoves. The target of this PKM activity output is the IKM of Sragen Regency to get knowledge and skills to use alternative energy biomass wood pellets as fuel